The Relevance of the al-Musâwâh Principle and the Law Prohibiting Monopolistic Practices in the Use of Digital Payments - Waldi Nopriansyah; Arne Huzaimah; Muhammad Salim (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Using a single digital payment application exclusively among business entities has adverse effects on economic activities, leading to the emergence of monopolistic practices. Therefore, the principle of al-Musâwâh (balance) is crucial in economic transactions. This study aims to elucidate the prohibition of monopolistic practices, advocate for the application of the al-Musâwâh principle in business operations, and explore its relevance in curbing monopolistic behaviours in the utilisation of digital payments across various business sectors. This research employs a qualitative approach through a literature review, focusing on normative analysis related to the al-Musâwâh principles and the prohibition of monopolistic practices in digital payments. The critical-comparative analysis method is utilised to critique and correlate the application of the al-Musâwâh principle with the prohibition of monopolistic practices. The findings indicate that businesses should adhere to the al-Musâwâh principle when utilising digital payment systems and refrain from exclusive partnerships with single payment platforms. Current practices where companies restrict themselves to one digital payment application contribute to monopolistic tendencies. Consequently, the Indonesian Competition Commission (KPPU) and the Government are urged to amend Law Number 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Business Competition promptly to effectively address issues in the digital economy